(NmATERIALY PO GEOLOGI^ESKOMU IZU^ENI@ tAMBUKANSKOGO OZERA (B:s (Ns (B2 (NTABLICAMI (B/s - (NsLAWQNOW(B, (NnIKOLAJ nIKOLAEKWI^s ((NlENINIGRAD (B:s (NiZD(B. (NgELOG(B. (NKOMITETA(B,s, 1926)
(NrEZ@ME NA FR(B. (NQZ(B. s
(NbIBLIOGR(B. (NW PODSTRO^ PRIME^(B.s
Keywords: (NgEOLOGIQs; (NgEOLOGI^ESKIE ISSLEDOWANIQs; (NtAMBUKANSKOE OZEROs